Smart Mobile Technologies in Math Education: Improving Elementary Students' Mathematical Communication Skills - Pasani, Chairil Faif; Amelia, Rizky (International journal of interactive mobile technologies, 2025)
Despite mathematics being a mandatory subject in elementary schools worldwide, it is often taught using traditional methods that emphasise rote memorisation, frequent homework assignments, and retention. These approaches can feel monotonous and tiresome for 21st-century students. This study investigates the use of interactive technology in selected elementary school math classrooms to explore its potential for enhancing students’ mathematical communication skills. The integration of technology in teaching methods has the potential to improve academic performance and foster excellent mathematical communication proficiency. Data were collected through a questionnaire administered to 30 fourth-grade students from two public elementary schools. The findings indicate that teachers recognise the significant role of interactive technologies in enhancing elementary students’ mathematical communication skills. Furthermore, participants demonstrated improved abstract communication and comprehension following the implementation of interactive learning sessions. The results highlight a clear positive impact of technology on students’ mathematics learning, particularly when applied in hands-on learning environments. Overall, the study concludes that incorporating interactive technologies in math education is more effective than traditional teaching methods, leading to higher academic performance, a deeper understanding of mathematical concepts, and improved student communication skills.